Formulation of Green Economy Based Business Strategy for Micro, Small and Medium Enterprises in Kupang City - Clara Margilina Reinamah; Deasy Susana Ratokoni Ndaparoka; Fransiskus Marlon Reu (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2025)
population will result in an increase in the volume of waste where if the waste is not managed properly it can cause various disturbances. This is the reason for the object of research on Micro, Small and Medium Enterprises (MSMEs), because MSMEs are the largest type of business in Indonesia and are also in direct contact with natural resources. The majority of MSMEs in Kupang City are engaged in the field of ikat weaving which uses fabric dyes, thus producing production waste in the form of liquid waste and other forms. The increase in the number of MSMEs can be a threat to increasing the potential for environmental pollution if the waste produced is not managed properly. Therefore, the concept of green economy is further analyzed to become the basis for implementing business activities, namely as a business strategy. Researchers used a sample of 30 fostered Ikat Weaving MSMEs in Kupang City, then simulated the formulation of business strategies with a green economy approach which showed that the ideal business strategy implemented by Ikat Weaving MSMEs in Kupang City is in zone 4 with a weighted average value of the EFE Matrix of 2.0 - 2.5. The results of the IE matrix mapping show that Kupang City MSMEs use a growth and build strategy, which consists of an intensive strategy or an integrative strategy.